2020
DOI: 10.1093/mmy/myaa024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Pneumocystis jirovecii pneumonia: A review of current methods and novel approaches

Abstract: Pneumocystis jirovecii can cause life-threatening pneumonia in immunocompromised patients. Traditional diagnostic testing has relied on staining and direct visualization of the life-forms in bronchoalveolar lavage fluid. This method has proven insensitive, and invasive procedures may be needed to obtain adequate samples. Molecular methods of detection such as polymerase chain reaction (PCR), loop-mediated isothermal amplification (LAMP), and antibody-antigen assays have been developed in an effort to solve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
105
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 163 publications
0
105
0
10
Order By: Relevance
“…Pneumocystis pnömonisi, HIV negatif genel durumu bozuk hastalarda mortalitesinin yüksek olması nedeniyle önemlidir. Yapılan çalışmalarda, HIV pozitif hastalarda mortalite %7-20'iken, HIV negatif genel durumu bozuk hastalarda mortalite %29-60 olarak bulunmuştur (25) . Bu nedenle, üçüncü basamak hastanelerde solunum yolu örneklerinde, özellikle altın standart olan BAL örneklerinde P. jirovecii'nin aranması gerekir.…”
Section: Discussionunclassified
“…Pneumocystis pnömonisi, HIV negatif genel durumu bozuk hastalarda mortalitesinin yüksek olması nedeniyle önemlidir. Yapılan çalışmalarda, HIV pozitif hastalarda mortalite %7-20'iken, HIV negatif genel durumu bozuk hastalarda mortalite %29-60 olarak bulunmuştur (25) . Bu nedenle, üçüncü basamak hastanelerde solunum yolu örneklerinde, özellikle altın standart olan BAL örneklerinde P. jirovecii'nin aranması gerekir.…”
Section: Discussionunclassified
“…These findings would be consistent with the lower Ct values observed in these samples, which might reflect a smaller burden of PJ organisms, thus resulting in false-negative results at the microscopic examination. Six of seven patients were patients not living with HIV ( Table 1 ), which is a condition notoriously associated with a larger burden of PJ organisms in respiratory samples [ 3 ]. Therefore, we did not interpret the seven IFA negative results as falsely PCR positive results but as the results of patients who had benefited from the molecular rather than the microscopic diagnosis of PCP [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The non-specificity of either respiratory symptoms or imaging features necessitates differentiation among possible infectious etiologies as well as between infectious and non-infectious respiratory abnormalities [ 1 ]. Molecular-based methods for detecting pneumonia agents in multiple or single assays have been developed to overcome the limits of conventional (microscopy- or culture-based) identification methods, which are familiar in medical mycology [ 2 ] especially with PJ organisms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This appears to be an even greater problem when BALF is tested, as noted in our study, and reported by others [ 12 ]. The reasons for false positive results are related, in part, to the sharing of similar glucans among various fungi and to similar substances on cellulose membranes, gauze packing material, and Gram-negative bacterial cell walls [ 14 ]. Why specificity is lower in BALF than serum is not clear.…”
Section: Discussionmentioning
confidence: 99%